Training practices and perceptions of soccer officials: Insights from the Referee Training Activity Questionnaire - McEwan, G. P.; Unnithan, V. B.; Easton, C.; Arthur, R. (International Journal of Sports Science & Coaching, 2023)
This study sought to: (1) document the multifaceted training practices of soccer officials in relation to their role and officiating category; and (2) explore the association between the officials` training practices and perceptions of the attributes pertinent to optimal performance. Field referees and assistant referees at officiating categories 1-3 (n = 173) with the Scottish Football Association were invited to participate in this national cross-sectional study. Using the Referee Training Activity Questionnaire (RTAQ), officials reported the volume and type of training engaged in during a 2-week in-season period. Respondents` perceptions of the skills pertinent to performance were also explored using a 7-point Likert scale (1 = not at all important; 7 = extremely important), with the frequency in which they trained these skills assessed using a 5-point Likert Scale (1 = less than once a month; 5 = more than once a week). Ninety-one responses were received, representing a 52.6% response rate. Irrespective of their role or level of professional attainment, the officials` training was focused mostly on physical conditioning, with significantly less time apportioned to decision-making (P < 0.001; ES = 1.28), psychological (P < 0.001; ES = 1.47), and technical (P < 0.001; ES = 1.23) skills training. Meanwhile, although decision-making and psychological skills were rated as "very important" to "extremely important" amongst both field referees and assistant referees, officials purposefully trained these skills "less than once a month." The present study provides important new insights into the training practices engaged in by soccer officials. As accurate decision-making is at the forefront of soccer officiating, enhancing the exposure of match officials to match-related decision-making during training should be considered a priority for future research.